The Value of Endoscopic Dacryocystorhinostomy in Management of Acquired Nasolacrimal Duct Obstruction - Ahmed Abdelaal (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: The epiphora is the most common manifestation of obstruction of the nasolacrimal duct, which is treated by dacryocystorhinostomy either by external or internal endoscopic endonasal approach. With the advance of the nasal endoscope, the endoscopic dacryocystorhinostomy became well established. Aim of the work: To evaluate the efficacy and safety of intranasal endoscopic dacryocystorhinostomy  [DCR]  in the management of patients with  acquired nasolacrimal duct obstruction. Patients and Methods: This is a retrospective study of patients with acquired obstruction of the nasolacrimal duct who underwent intra-nasal endoscopic dacryocystorhinostomy [EDCR] at Al-Azhar University Hospitals from September 2012 to October 2015. Forty-five procedures were done where primary endoscopic DCR was done on forty patients and revision endoscopic DCR was done on failed five patients. The outcome is measured by subjective improvement of epiphora. Results: The patients were followed up for three years, improvement of 35 patients with epiphora from  40 patients [the rate of success was 86.7%] and the remaining five failed cases undergoing revision EDCR with the improvement of four from them. The success was confirmed with the subjective improvement of epiphora. The rate of minor complications reported was 28.8% and managed conservative, and only one major complication occurred in one patient. Conclusion: The endoscopic intranasal DCR is an effective and safe procedure in the management of acquired obstruction of the nasolacrimal duct and gives a high success rate.